Animals, Cameras, Humans – A Technological Love Triangle? - Cortés-Zulueta, Concepción (My University, 2018)
Nowadays, there appears to be a visual and technological love triangle between humans, cameras and other animals, widely broadcasted through internet and its social networks. Depending on the occasion, the distances and relationships between the elements of this triangle change, as the three of them try either to approach, chase or flee from one another.
Animales, cámaras, humanos - ¿Un triángulo amoroso tecnológico?
Keywords: Animales; Humanos; Cámaras; Humanos; Distancia; Triángulo; Cultura visual; Estudios animales; Vídeos; Internet